Ploidy Testing of Blastocoel Fluid for Screening May Be Technically Challenging and More Invasive Than That of Spent Cell Culture Media - Shi, Wenhao; Zhao, Zhenghao; Xue, Xia; Li, Qian; Yao, Yaxin; Wang, Dongyang; Wang, Jing; Lu, Sijia; Shi, Juanzi (Frontiers in Physiology, 2022)
Background: Recent studies have demonstrated that both blastocoel fluid (BF) and spent cell culture media (SCM) have potential as materials for non-invasive or less-invasive preimplantation genetic analysis. BF may allow more opportunity to obtain cell-free DNA from the inner cell mass (ICM), and it has a lower risk of containing contaminant DNA from cumulus cells, sperm and culture media. There are no data regarding the ICM as a gold standard to evaluate the chromosome constitution of BF or SCM for embryo liquid biopsy. Methods: Two hundred eighteen donated human blastocysts were warmed and cultured in blastocyst culture media for 18-24 hours. The corresponding SCM was collected, and only clear ICM was biopsied in blastocysts; otherwise, the whole blastocyst (WB) was biopsied. Quantitative PCR was performed to determine the DNA levels in the SCM and BF before and after amplification. ChromInst was used to amplify BF/SCM and blastocyst DNA before sequencing. Chromosomal copy number variation (CNV) was investigated to evaluate the chromosome constitution. Results: In total, 212 blastocysts were available for SCM and BF collection. The technical success rates (next-generation sequencing data) were 100% and 69.8% (148/212) for SCM and BF, respectively. Among the 148 blastocysts with both SCM and BF data, 101 were euploid and 47 were aneuploid based on ICM (n = 89) or WB (n = 59) analysis as the gold standard. Among all blastocysts, SCM was comparable to BF [specificity: 80.2% versus 61.4% (P = 0.005, χ² test); sensitivity: 91.5% versus 87.2% (P = 0.738, χ² test); negative predictive value (NPV): 95.3% versus 91.2% (P = 0.487, χ²test); positive predictive value (PPV): 68.3% versus 51.3% (P = 0.042, χ² test)]. The SCM and BF samples were 83.8% (124/148) and 69.6% (103/148) concordant with the corresponding ICM/WB samples when only two categories, euploid or aneuploid/mosaic, were grouped to calculate the concordance. Conclusions: Compared with BF, SCM has superior diagnostic performance, and it is noninvasive for embryos. Clinical Trial registration: (http://www.chictr.org.cn; ChiCTR-BPD-17014087).